Moderasi Sales Growth terhadap Penghindaran Pajak di Perusahaan Sektor Energi - Mediaty, Mediaty; Usman, Asri; Khaerany, Rizky; Arman, Rifqah Zakiyah; Tandilino, Charles (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
In management accounting practice, companies have the ability to choose accounting policies to improve the company's financial performance. Some schemes transfer pricing between affiliates and profit management using discretionary accrual methods. Both of these practices are used to optimize post-tax profits. The study aims to analyze the impact of transfer pricing and profit management moderated by sales growth on tax avoidance practices of energy sector companies listed on the Indonesian Stock Exchange. The research method used is a descriptive method with data analysis techniques i.e. moderated regression analysis using purposive sampling so that the number of samples used is 43 companies registered on Indonesia Stock Exchange in the period 2021-2023. In this study it was found that sales growth reinforces the negative influence of transfer pricing on tax avoidance practices. The next research finds that sales growth does not moderate the influence of profit management on tax avoidance practices carried out by companies. Moreover, without sales growth moderation, transfer pricing and profit management have no significant influence on tax avoidance practices.